THE IMPACT OF ZAKAT EMPOWERMENT ON THE FOOD SECURITY SECTOR IN EAST JAVA - Arief Hidayat Amuda; Siti Inayatul Faizah (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to know about the optimization of the zakat empowerment concept in the food security sector in East Java. This research uses qualitative descriptive and the analysis technique uses Creswell theory. The object in this study is Wayahe Tanhdur program from LAZ Nurul Hayat which is located at krangkong village Bojonegoro East java. The results of this study are Wayahe Tanhdur program from LAZ Nurul Hayat has successfully carried out an empowerment process as evidenced by each member of the farmer who is part of the Wayahe Tanhdur program that has successfully carried out the harvest process with a term of the agreement. However, to form an independent mustahiq farmer class cannot be achieved by the Wayahe Tanhdur program and is expected to be an evaluation for the Wayahe Tanhdur program.Keywords: zakat empowerment, Wayahe Tanhdur Program, food security, LAZREFFERENCE Ali, Muhammad Daud. (1998). Sistem ekonomi Islam zakat dan wakaf. Jakarta: Universitas Indonesia Press.Badan Ketahanan Pangan. (2017). Ketersediaan pangan 2010-2017. Jakarta: Kementan.Dewan Ketahanan Pangan, Kementrian Pertanian dan World Food Programme (WFP). (2015). Food security and vulnerability atlas of Indonesia 2015. Jakarta: Kementan.FAO (Food and Agriculture Organization of the United Nations). (2012). The Stateof Food and Agriculture. Geneva: FAO.Mukhopadhyay, Kakali. (2018). Food security in China at 2050: a global CGE exercise. Journal of Economic Structures, 7(1), 1-29.Timmer C.Peter. (2017). Food Security, Structural Transformation, Markets andGovernment Policy. Asia & the Pacific Policy Studies, 4(4), 1-16. Doi: 10.1002/app5.161.Nurul Huda dan Mohamad Heykal. (2010). Lembaga keuangan Islam tinjauan teoritis dan praktis, Jakarta: Kencana.Prastiawati, F., & Darma, E. S. (2016). Peran pembiayaan Baitul Maal Wat Tamwil terhadap perkembangan usaha dan peningkatan kesejahteraan anggotanya dari sektor mikro pedagang pasar tradisional. Jurnal Akuntansi dan Investasi, 17(2), 197-208.Rachman, Mochammad, Syed Othman Alhabshi, Shaikh Hamzah Abdul Razak. (2015). Peran warung mikro bank syariah mandiri kudus dalam pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) di Kudus. Jurnal Equilibrium, 3(2), 271-289.